1994
DOI: 10.1177/039139889401700604
|View full text |Cite
|
Sign up to set email alerts
|

Dialyser Reuse: An Automated System Using Peracetic Acid

Abstract: For 3 years starting in April 1989, in a 17-station, in-centre haemodialysis unit at the Toronto Western Hospital, re-use of dialysers was performed using the Renatron-2 Dialyser Reprocessing System with peracetic acid as a sterilant. During this period 40,234 treatments were carried out and dialysers were used an average of 4.2 times. Net savings, after taking into account the total costs of re-use, averaged Can $309,000,000 per year. There were no deaths and no discernible morbidity attributable to the pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…An analysis from Canada published around the same time revealed a modest saving of not higher than Canadian $739 per patient per year when using a lower cost heated citric acid disinfectant in the reprocessing system . This estimate was substantially less than earlier 1990s reports from Canadian practices suggesting that the economic benefit of reuse may have gone down over time with the increasing availability of cheaper high‐flux dialyzers . In addition, Fresenius Medical Care, a large integrated company with dialyzer manufacturing and dialysis service delivery components, moved to single‐use only practice in early 2000s arguing that the cost related to reuse is equal to or greater than the cost of a new biocompatible dialyzer .…”
Section: Dialyzer Reuse and Impact On Cost Of Carementioning
confidence: 87%
“…An analysis from Canada published around the same time revealed a modest saving of not higher than Canadian $739 per patient per year when using a lower cost heated citric acid disinfectant in the reprocessing system . This estimate was substantially less than earlier 1990s reports from Canadian practices suggesting that the economic benefit of reuse may have gone down over time with the increasing availability of cheaper high‐flux dialyzers . In addition, Fresenius Medical Care, a large integrated company with dialyzer manufacturing and dialysis service delivery components, moved to single‐use only practice in early 2000s arguing that the cost related to reuse is equal to or greater than the cost of a new biocompatible dialyzer .…”
Section: Dialyzer Reuse and Impact On Cost Of Carementioning
confidence: 87%
“…This economic evaluation contrasted a 1993 Canadian study that showed savings of up to CAN $3629 per patient per year with five reuses using formaldehyde (36). Other studies from this same period also noted significant financial benefit with reuse, with one reporting 95% savings on high-flux dialyzer cost with 20 reuses (37) and another reporting savings of CAN $309 thousand annually to a Canadian hospital with an average of four reuses (38). These discrepancies highlight the need to reexamine the extent of economic benefit with reuse in the context of increased availability of cheaper high-flux dialyzers and rising cost of personnel and space.…”
Section: Economics Of Dialyzer Reusementioning
confidence: 97%